Non-vaccine strategies for cholera prevention and control: India's preparedness for the global roadmap. (29th February 2020) - Das, Madhuchhanda; Singh, Harpreet; Girish Kumar, C.P.; John, Denny; Panda, Samiran; Mehendale, Sanjay M.
Abstract: Background: Recently World Health Organization's Global Task Force on Cholera Control (GTFCC) has published a global roadmap for prevention and control of cholera. We review preparedness of existing governmental non-vaccine programs and strategies for cholera prevention and control in India. We also describe strengths and gaps in the context of implementation of the global roadmap. Methods: We reviewed published literature on non-vaccine based strategies for prevention and control of cholera in India and analyzed strengths and weaknesses of Government of India's major anti-cholera and ante-diarrhea initiatives under Integrated Disease Surveillance Program (IDSP), National Rural Health Mission (NRHM), and other disease surveillance platforms. Results: The first strategy of the WHO global roadmap, namely, preparedness for early detection and outbreak containment, has been addressed by the IDSP. NRHM complements IDSP activities by focusing on sanitation, hygiene, nutrition, and safe drinking water. We identified the need to adopt stricter case definitions and data validation protocols. Multi-sectoral approach to prevent cholera occurrences and re-occurrences [the second suggested strategy in the global roadmap], highlights identification of hotspots and implementing strategies based on transmission dynamics. We recommend development of comprehensive models by integrating data sources beyond the national programs to eliminate cholera hotspots in India. Implementing the third proposed strategy in the global roadmap, coordinated technical support, resource mobilization, and partnerships at local and global levels, has major challenges in India due to structural issues related to health systems and health programs. Conclusion: Even with a robust public health infrastructure, absence of a national cholera program might have resulted in lack of specific focus and concerted efforts for cholera prevention and control in India. A National Taskforce for Cholera Control must develop India-specific 'National Cholera Prevention and Response Road Map' with an appropriate administrative and financially viable framework for its implementation.